2018
DOI: 10.2337/dc18-0384
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Carriers of the HNF1A p.E508K Variant Do Not Experience an Enhanced Response to Sulfonylureas

Abstract: Carriers of variant p.E508K in have a reduced insulin response rather than the increased sensitivity to sulfonylureas seen in patients with MODY3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Notably, a study on the short-term response to the sulphonylurea glipizide showed that neither non-diabetic nor diabetic carriers of the Mexican/US Latino HNF1A E508K variant were sensitive to sulphonylurea stimulation. 75 Genome-wide meta-analysis also does not implicate any common HNF1A variants in the glycemic response to sulphonylurea treatment. 76 Whether carriers of the c.1108G>T variant could benefit from treatment with sulphonylurea should be pursued within the context of a randomised clinical trial establishing both short and long-term efficacy of sulphonylurea in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a study on the short-term response to the sulphonylurea glipizide showed that neither non-diabetic nor diabetic carriers of the Mexican/US Latino HNF1A E508K variant were sensitive to sulphonylurea stimulation. 75 Genome-wide meta-analysis also does not implicate any common HNF1A variants in the glycemic response to sulphonylurea treatment. 76 Whether carriers of the c.1108G>T variant could benefit from treatment with sulphonylurea should be pursued within the context of a randomised clinical trial establishing both short and long-term efficacy of sulphonylurea in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with p.His126Asp do not respond to sulfonylureas (low and high doses), dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors), or glucagon-like peptide-1 receptor agonists (GLP-1Raa), also known as incretin analogs ( 75 ). Low-dose sulfonylurea therapy is the first-line therapy for MODY3 but does not show special sensitivity to HNF1α-related T2D ( 76 ). For example, Mexican carriers of the HNF1α p.E508K variant have no increased sensitivity to sulfonylureas ( 76 ).…”
Section: Association Between Hnf1a Polymorphism and Mody3mentioning
confidence: 99%
“…Low-dose sulfonylurea therapy is the first-line therapy for MODY3 but does not show special sensitivity to HNF1α-related T2D ( 76 ). For example, Mexican carriers of the HNF1α p.E508K variant have no increased sensitivity to sulfonylureas ( 76 ).…”
Section: Association Between Hnf1a Polymorphism and Mody3mentioning
confidence: 99%
“…A second challenge is the difficulty to evaluate the pathogenicity of genetic variants (7), for which there is also an on-going international effort to establish guidelines and provide expert variant curations in the ClinVar database (clinicalgenome.org/affiliation/50016) (8). Furthermore, the response to alternative treatment might differ between populations (9). One of the ways to address the challenge of precise diagnostics is to complement genetic screening with additional data, combining both molecular and clinical dimensions (10).…”
Section: Introductionmentioning
confidence: 99%